Canada's GINGOs: who are they, what are they doing, and what role for the future?. Issue 6 (17th August 2020) - Davis, John-Michael
ABSTRACT: International NGOs (INGOs) in the global North have rapidly grown in number over the past two decades, the majority of which are grassroots organisations (GINGOs). Despite an abundance of research on "professionalised" INGOs, little empirical data is available to characterise GINGOs. This study constructs a dataset of 607 Canadian GINGOs based on the Canada Revenue Agency T3010 forms and organisation websites to answer three broad questions of GINGOs: Who are they? What is their programmatic foci? Where do they operate? The results offer a rich portrayal of GINGOs and situates their current and potential contributions towards international development goals.